L'archeologia preventiva: documentazione, formazione e comunicazione - Calandra, Elena (GEOmedia, 2024)
The preventive assessment of archaeological interest is law in Italy since 2005, but was practised since well before: it is the normative and scientific medium that regulates the relationship between public works and archaeology, and as such needs to be properly communicated by the archaeologists in charge, so as to interest and involve citizens.